RHIZOME BANGLE EXTRACT INHIBITION GROWTH TEST AGAINST Staphylococcus aureus FOR ORAL ABSCESSS HERBAL TREATMENT (UJI DAYA HAMBAT EKSTRAK RIMPANG BANGLE TERHADAP PERTUMBUHAN Staphylococcus aureus SEBAGAI PERAWATAN HERBAL ABSES ORAL) - Putu Sulistiawati Dewi; Setiawan (Journal of Health and Dental Sciences, 2022)
An abscess is a typical infection caused by Staphylococcus aureus bacteria. Resistance of bacteria occurs due to improper antibiotics dosage, inaccurate diagnosis, and improper bacterial causes. Rhizome Bangle contains saponins, flavonoids and essential oils, alkaloids, tannins, and glycosides that have antibacterial. The purpose of this study is to determine the inhibitory effect of rhizome Bangle extract (Zingiber purpureum Roxb.) on the growth of Staphylococcus aureus bacteria in Vitro. The study was an experimental laboratory study with group design post-test in vitro. The method used as the antibacterial test was the Kirby Bauer diffusion method. Concentration of rhizome Bangle extract were 8%, 16%, 32%, and negative control of ethanol and positive control of chlorhexidine 0,2%. The culture medium used Mueller Hinton agar (MHA). Data  analyzed by Krusskal wallis (p <0.05). The result of this study shows Rhizome Bangle extract 32% concentration inhibit Staphylococcus aureus bacteria growth significant with p= 0.001. The conclusion is that rhizome Bangle extract (Zingiber purpureum Roxb.) inhibits the growth of Staphylococcus aureus bacteria at 32% concentration. DOI : 10.54052/jhds.v1n3.p225-232